An initial psychometric assessment of an ICD-11 based measure of PTSD and complex PTSD (ICD-TQ): Evidence of construct validity. (December 2016) - Karatzias, Thanos; Shevlin, Mark; Fyvie, Claire; Hyland, Philip; Efthymiadou, Erifili; Wilson, Danielle; Roberts, Neil; Bisson, Jonathan I.; Brewin, Chris R.; Cloitre, Marylene
Highlights: Confirmatory factor analysis supported the factorial validity of the ICD-TQ. ICD-TQ demonstrated satisfactory internal reliability. ICD-TQ exhibited convergent and discriminant validity. Abstract: Among the conditions following exposure to traumatic life events proposed by ICD-11 are Posttraumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD). The primary aim of this study was to provide an assessment of the reliability and validity of a newly developed self-report measure of ICD-11 PTSD and CPTSD: the ICD-11 Trauma Questionnaire (ICD-TQ). Participants in this study were a sample of individuals who were referred for psychological therapy to a National Health Service (NHS) trauma centre in Scotland ( N  = 193). Participants completed the ICD-TQ and measures of traumatic life events, DSM-5 PTSD, emotion dysregulation, self–esteem, and interpersonal difficulties. Confirmatory factor analysis results supported the factorial validity of the ICD-TQ with results in line with ICD-11 proposals. The ICD-TQ demonstrated satisfactory internal reliability, and correlation results indicated that the scale exhibited convergent and discriminant validity. Current results provide initial support for the psychometric properties of this initial version of the ICD-TQ. Future theoretical and empirical work will be required to generate a final version of the ICD-TQ that will match the diagnostic structure of PTSD and CPTSD when ICD-11 is published.